A new IDH-independent hypermethylation phenotype is associated with astrocyte-like cell state in glioblastoma - Simões Costa, Ana Luísa; Dončević, Daria; Wu, Yonghe; Yang, Lin; Man, Ka Hou; Spreng, Anna-Sophie; Winter, Hannah; Fletcher, Michael Nai Chung; Radlwimmer, Bernhard; Herrmann, Carl (Genome biology, 2025)
Background: DNA methylation plays a crucial role in cancer development and pro‑gression and has been linked to genetically and clinically distinct tumor classes, including IDH‑mutated and IDH‑wildtype adult‑type diffuse gliomas. Here, we identify a CpG‑island methylator phenotype (CIMP) that characterizes the receptor tyrosine kinase 2 (RTK2) subtype of IDH‑wildtype glioblastoma. - Results: This RTK2‑CIMP affects genomic locations and cell functions distinct from those of IDH mutation‑associated IDH‑CIMP and suppresses the expression of its target genes. The RTK2‑CIMP‑region chromatin is characterized by a combina‑tion of repressive and activating marks, including polycomb‑associated H3K27me3 and enhancer‑associated H3K4me1, consistent with DNA methylation‑mediated silencing of genes with bivalent‑state promoters in neural progenitor cells. Func‑tionally, RTK2‑CIMP affects neuronal lineage genes and is significantly associated with astrocyte‑like glioblastoma, suggesting that RTK2‑CIMP is an epigenetic signature of the astrocyte‑like cell state. Furthermore, we demonstrate that RTK2‑CIMP can be induced by genetic manipulation in glioblastoma cells. - Conclusions: Our results suggest that RTK2‑CIMP is a key contributor to cell‑state plasticity in glioblastoma.
Gesehen am 04.12.2025